Correlation of Between Hemoglobin Level Of Pregnant Women With Birth Weight Of Infants - Rahmi Fitria; Nana Aldriana; Sri Wulandari; Eka Yuli Handayani; Andria Andria (Universitas Aisyah Pringsewu, 2023)
The availability of healthy body and its normal weight, it is expected that it will be done because of the birth weight of the newborn baby child which can affect these things immediately after birth. which can affect anyone. For example, birth weight is measured in terms of micronutrients, especially iron, anemia that occurs clearly but is not treated, serious problems such as premature birth. . Obtaining iron to be able to provide small amounts of iron to the fetus is essential for normal iron metabolism. The mother's hemoglobin level falls below 11 g/dL during the third trimester. Anemia in pregnant women can cause a lack of oxygen in the body and can prevent the growth of the fetus, and make the chances of pregnancy and the baby less. The purpose of this study is to determine the corrrelation between the hemoglobin level of mother in pregnancy and birth weight in the city of Tambusai Timur in 2022. is a linear regression. The sample in this study is mothers in the third trimester who are about to give birth in Tambusai Timur city using a comprehensive sampling method about 54 respondents. The results of this study showed that there is a significant corrrelation between the Hb levels of mother in pregnancy and the weight of newborns. This is one of the general and the most important of the Potosibau Maplelors. (p = 0.045). Suggestions for respondents to routinely check the nearest health service, to monitor the mother's Hemoglobin level during pregnancy in order to monitor the development of the baby in the mother's womb. Abstrak: Berat badan lahir bayi adalah penimbangan berat badan bayi segera setelah lahir, salah satu faktor yang dapat mempengaruhi berat badan lahir bayi, misalnya pengukuran dalam bentuk zat gizi mikro terutama zat besi, anemia yang terjadi secara signifikan dan tidak diobati, dapat meningkatkan risiko komplikasi serius, seperti kelahiran prematur bayi. . Pengambilan zat besi sehingga hanya memberikan sedikit zat besi pada janin diperlukan untuk metabolisme zat besi yang normal. Kadar hemoglobin ibu turun di bawah 11 g/dl selama trimester ketiga. Anemia pada ibu hamil dapat mengakibatkan kekurangan oksigen ke jaringan dan akan mengganggu pertumbuhan janin, serta dapat meningkatkan risiko persalinan prematur dan bayi berat lahir rendah. Tujuan penelitian ini adalah untuk mengetahui hubungan kadar hemoglobin ibu hamil dengan berat badan bayi baru lahir di Desa Tambusai Timur Tahun 2022. Jenis penelitian ini adalah kuantitatif analitik dengan desain cross sectional study, uji statistik yang digunakan adalah Regresi Linier. Sampel dalam penelitian ini adalah ibu hamil trimester III yang akan bersalin di Desa Tambusai Timur sebanyak 54 responden dengan menggunakan teknik sampling jenuh. Hasil penelitian ini menunjukkan bahwa ada hubungan antara kadar HB ibu hamil dengan berat badan bayi baru lahir dengan nilai (p = 0,045). Saran bagi responden agar rutin memeriksakan diri ke pelayanan kesehatan terdekat, memantau kadar hemoglobin ibu selama hamil agar dapat memantau perkembangan bayi dalam kandungan ibu.